Cosmological perfect-fluids in f(R) gravity - Capozziello, Salvatore; Mantica, Carlo Alberto; Molinari, Luca Guido (International journal of geometric methods in modern physics, 2019)
We show that an n -dimensional generalized Robertson–Walker (GRW) space-time with divergence-free conformal curvature tensor exhibits a perfect fluid stress–energy tensor for any f ( R ) gravity model. Furthermore, we prove that a conformally flat GRW space-time is still a perfect fluid in both f ( R ) and quadratic gravity where other curvature invariants are considered.